Visual and refractive outcomes of small incision lenticule extraction for the correction of myopia: 1-year follow-up. Issue 11 (26th November 2015) - Kamiya, Kazutaka; Shimizu, Kimiya; Igarashi, Akihito; Kobashi, Hidenaga
Abstract : Objective: To assess the 1 year clinical outcomes of small incision lenticule extraction (SMILE) for the correction of myopia and myopic astigmatism using a 500 kHz femtosecond laser system. Methods: This prospective study evaluated 52 eyes of 39 consecutive patients (31.8±6.9 years, mean age±SD) with spherical equivalents of −4.11±1.73 D (range, −1.25 to −8.25 D) who underwent SMILE for myopia and myopic astigmatism. Preoperatively, 1 week, and 1, 3, 6 and 12 months postoperatively, we assessed the safety, efficacy, predictability, stability, corneal endothelial cell loss and the adverse events of the surgery. Results: The logarithm of the minimal angle of resolution (logMAR) uncorrected distance visual acuity and LogMAR corrected distance visual acuity were −0.16±0.11 and −0.22±0.07, respectively, 1 year postoperatively. At 1 year, all eyes were within±0.5 D of the targeted correction. Manifest refraction changes of −0.05±0.32 D occurred from 1 week to 1 year postoperatively (p=0.20, Wilcoxon signed-rank test). The endothelial cell density was not significantly changed from 2804±267 cells/mm 2 preoperatively to 2743±308 cells/mm 2 1 year postoperatively (p=0.12). No vision-threatening complications occurred during the observation period. Conclusions: SMILE performed well in the correction of myopia and myopic astigmatism, and no significant change in endothelial cell density or any other serious complications occurred throughout the 1-year follow-up period, suggesting its viability as a surgical option for the treatment of such eyes.